GAMBARAN PENGETAHUAN TENTANG ASPEK PRE-TRAVEL CARE DALAM KEPERAWATAN PARIWISATA PADA MAHASISWA KEPERAWATAN TAHAP AKHIR SARJANA DI UNIVERSITAS UDAYANA - Tataraharja, I Putu Langgeng Sugih; Damayanti, Putu Ayu Asri; Rahajeng, Indah Mei (Coping: Community of Publishing in Nursing; Vol 12 No 2 (2024): April 2024DO - 10.24843/coping.2024.v12.i02.p02, 2024)
Travel Health Nursing (THN) is a nursing specialty that plays a role in preventing health problems for travelers. Before traveling, travelers should make pre-travel care preparations which include a risk assessment based on the information about the traveler and the itinerary so that prevention and self treatment can be carried out. This study aims to describe the knowledge of nursing students in the final stages regarding aspects of pre-travel care in THN at PSSKPPN Unud. This study used a cross-sectional descriptive design. Sampling in this study used a simple random sampling technique with a total sample of 53 final year nursing students. Data collection in this study used a knowledge questionnaire about Pre-Travel care aspects including the dimensions of traveler information, traveler itinerary also prevention and self-treatment. Data analysis used statistical tests of frequency distribution and central tendency. The results of this study indicated that the majority of respondents are female (86,1%) and the age range is 21-23 years. The level of knowledge about pre-travel care in THN is poor (37,7%), sufficient (43,4%), and good (18,9%). The researcher recommends strengthening the concept of pre-travel care to nursing students comprehensively through intra and extracurricular activities.